Antlered richardiid flies: new species of Richardia (Tephritoidea: Richardiidae) with antler‐like genal processes. Issue 2 (April 2015) - Wendt, Lisiane D.; Ale‐Rocha, Rosaly
Abstract Within Richardiidae, Richardia infestans, from Colombia, is the only known species to have genal processes, which are structures formed by the extension of the cuticle on the lateral margin of the gena. In the present work, six new species, with different patterns of antler‐like genal processes, are described. An identification key and illustrations are provided. Richardia bellasp. nov., R. modestasp. nov. and R. vittasp. nov. are recorded from Costa Rica; R. advenasp. nov. is recorded from Costa Rica and Panama; R. simplexsp. nov. is recorded from Panama; and R. ornatellasp. nov. is recorded from Ecuador.